2018
DOI: 10.1097/md.0000000000013537
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lymphovascular invasion in patients with prostate cancer following radical prostatectomy and its association with their clinicopathological features

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…Recently, mounting evidence has indicated that LVI is associated with poor prognosis for many types of tumors, such as liver, bladder, and prostate cancer (7,44). Jiang et al (6) reported that LVI is an independent prognostic factor for predicting worse progression in prostate cancer, and they recommended that LVI should be reported in the final pathological diagnosis after radical prostatectomy. Similarly, Canter et al (45) found that the presence of LVI in the final pathological reports for bladder cancer delivers significant risks for worse CSS and OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mounting evidence has indicated that LVI is associated with poor prognosis for many types of tumors, such as liver, bladder, and prostate cancer (7,44). Jiang et al (6) reported that LVI is an independent prognostic factor for predicting worse progression in prostate cancer, and they recommended that LVI should be reported in the final pathological diagnosis after radical prostatectomy. Similarly, Canter et al (45) found that the presence of LVI in the final pathological reports for bladder cancer delivers significant risks for worse CSS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphovascular invasion (LVI), which is defined as the presence of tumor cells within lymphatic or vascular channels, is a significant step in tumor distant metastasis (5,6). According to the recommended European urology guidelines, LVI is an independent prognostic factor for bladder cancer using cystectomy specimens (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mounting evidences have indicated that LVI is associated with poor prognosis for many kinds of tumors, such as liver, bladder, and prostate cancer [43,6]. Jiang et al [5] reported that LVI is an independent prognostic factor to predict worse progression in prostate cancer, and they recommended that LVI should be reported in the final pathological diagnosis after radical prostatectomy. Similarly, Canter et al [44] found that the presence of LVI in the final pathological reports for bladder cancer deliver significant risks for worse CSS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphovascular invasion, which defined as the presence of tumor cells within lymphatic or vascular channels, is a significant and crucial step in tumor distant metastasis [4,5]. The prognostic value of LVI has been established for bladder cancer, and European guidelines recommend the description of LVI in cystectomy specimens as an independent prognostic factor [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although not all margin-positive patients experience BCR, the presence of a positive surgical margin is a well-established risk factor for BCR 29 . The presence of lymphovascular invasion is also considered as a potential risk factor for BCR 30 . However, after adjusting for all confounding factors, only the 'overweight' group showed significant correlation between lymphovascular invasion and BCR.…”
mentioning
confidence: 99%